2010
DOI: 10.1002/jbmr.52
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α's effects on proliferation and apoptosis in human mesenchymal stem cells depend on RUNX2 expression

Abstract: RUNX2 is a bone-specific transcription factor that plays a critical role in prenatal bone formation and postnatal bone development. It regulates the expression of genes that are important in committing cells into the osteoblast lineage. There is increasing evidence that RUNX2 is involved in osteoblast proliferation. RUNX2 expression increases during osteoblast differentiation, and recent data even suggest that it acts as a proapoptotic factor. The cytokine tumor necrosis factor a (TNF-a) is known to modulate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…Opposing effects of TNF-a on MSC proliferation have also been reported. Boker et al reported that TNF-a caused an increase in the invasive and proliferative properties of human bone marrow-derived mesenchymal stem cells (hBMSCs) [12], but Ghali et al reported that TNF-a induced an inhibition of the proliferative and apoptotic properties of hBMSCs [13].…”
Section: Introductionmentioning
confidence: 99%
“…Opposing effects of TNF-a on MSC proliferation have also been reported. Boker et al reported that TNF-a caused an increase in the invasive and proliferative properties of human bone marrow-derived mesenchymal stem cells (hBMSCs) [12], but Ghali et al reported that TNF-a induced an inhibition of the proliferative and apoptotic properties of hBMSCs [13].…”
Section: Introductionmentioning
confidence: 99%
“…A study of the literature suggests that analysis of the involvement of osteoblasts in periprosthetic osteolysis has generally been limited to direct suppressive effect of particles on osteoblasts rather than through consideration of the possible effects of a pro-inflammatory environment on osteoblast biology. Considering that TNF-is also a potent inhibitor of osteoblast differentiation (Ghali et al, 2010;Yamazaki et al, 2009;Zhou et al, 2006;Karmakar et al 2010), additional investigations into possible involvement of particleactivated macrophages in the impaired osteogencity mediated by proinflammatory cytokines including TNF-would appear to be warranted. Although insufficient attention has been paid to the involvement of osteoblast, the cell type responsible for bone formation, more research should be conducted to delineate the potentially critical role of osteoblasts in periprosthetic osteolysis.…”
Section: Inflammatory Response In Particle Diseasementioning
confidence: 99%
“…So far, most researches in terms of involvement of osteoblast in periprosthetic osteolyis have been limited to determine the direct suppressive effect of particle to osteoblast. However, the possibility that osteoblast can indirectly communicate with immune cells through many sectreted molecules such as TNF-, IL-1, ROS requires further exploration (Ghali et al, 2010;Yamazaki et al, 2009;Zhou et al, 2006). Following phagocytosis of particles and the resultant pro-inflammatory reaction, the released cytokines from macrophages can be regarded as a potent inhibitor of osteoblast differentiation.…”
Section: Impaired Osteogenesis As An Inflammatory Reaction In Peripromentioning
confidence: 99%
“…Opposing effects of TNF-α on MSC proliferation have also been reported. Boker et al [6] and Kim et al [14] reported that TNF-α increase the invasive and proliferative properties of human bone marrow-derived mesenchymal stem cells (hBMSCs), but Ghali et al reported conflicting results that TNF-α inhibit the proliferative and apoptotic properties of hBMSCs [15]. This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction.…”
Section: Introductionmentioning
confidence: 97%